Analisis Perubahan Kadar BOD dan DO pada Air Buangan Industri Tahu dengan Pemberian Probiotik Lokal terhadap Perbedaan Waktu Inkubasi Interval 8 Jam - Kristian Harris; Budi Utomo; Koesdaryani Soeryodarundio (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The tofu industry in Indonesia generally utilizes simple processing technologies, leading to unresolved wastewater management issues. Tofu wastewater contains high organic matter, measured by BOD, a parameter indicating the oxygen required by microorganisms to decompose organic matter. High BOD can decrease dissolved oxygen (DO) levels in water, which is crucial for aquatic life. This study investigates the effectiveness of local probiotics in reducing BOD and increasing DO in tofu wastewater (ABIT). Three treatments were applied: pure ABIT, neutralized ABIT (ABIT-N), and ABIT mixed with local probiotics in three ratios (1:1, 1:2, and 1:3). DO was tested at 0, 8, 16, 24, and 36 hours, while BOD was tested at 0 and 5 days. The results demonstrate that local probiotics can effectively reduce BOD and enhance DO levels in ABIT. The highest DO (3.36 mg/L) was observed in ABIT-N mixed with local probiotics at a 1:3 ratio after 32 hours. The most significant BOD reduction (135.77 mg/L) was also achieved at the 1:3 ratio. These findings suggest that local probiotics offer an eco-friendly approach to treating tofu wastewater.